Can mean platelet volume (MPV) and platelet/lymphocyte ratio - Gokden, Yasemin; Kutlu, Orkide (Annals of Medical Research, 2021)
Aim: Investigating serum mean platelet volume (MPV) and platelet/lymphocyte ratio (PLR) levels in acute pancreatitis (AP) patients, and evaluating whether MPV and PLR estimate AP disease severity efficiently at early phase.Material and Methods: One hundred and forty patients diagnosed with AP and 49 healthy controls (HC) have been included in the study. Ranson criteria, revised Atlanta criteria and Balthazar scores of AP patients have been found from hospital registration systems, and mild-severe AP patients have been separated. MPV and PLR levels at admission were checked for the patients.Results: While no difference was determined between AP group and HC group with regard to MPV levels (p:0.998), PLR levels was determined to be higher in AP group than HC group (p0.001). No difference was determined between mild-severe AP patients with regard to MPV according to Ranson criteria, revised Atlanta criteria and Balthazar scoring (p:0.355; p:0.276; p:0.634, respectively). PLR was determined to be higher in severe AP group according to revised Atlanta criteria (p:0.023). However, no relation was determined between PLR and Ranson and Balthazar scoring (p:0.311, p:0.415, respectively). Upon grouping AP patients as biliary and non-biliary according to their etiology, MPV was determined to be lower in non-biliary AP patients (p:0.034). There was no difference between groups with regard to PLR (p:0.0772).Conclusion: MPV is not suitable for differentiating mild-severe AP patients at early period. PLR may be used as a supporting test in estimating severe AP patients at admission.
Keywords: Acute; mild; MPV; pancreatitis; PLR; severe